Diversity of genetic backgrounds modulating the durability of a major resistance gene. Analysis of a core collection of pepper landraces resistant to Potato virus Y. (17th June 2015) - Quenouille, Julie; Saint‐Felix, Ludovic; Moury, Benoit; Palloix, Alain
Summary: The evolution of resistance‐breaking capacity in pathogen populations has been shown to depend on the plant genetic background surrounding the resistance genes. We evaluated a core collection of pepper ( Capsicum annuum ) landraces, representing the worldwide genetic diversity, for its ability to modulate the breakdown frequency by Potato virus Y of major resistance alleles at the pvr2 locus encoding the eukaryotic initiation factor 4E (eIF4E). Depending on the pepper landrace, the breakdown frequency of a given resistance allele varied from 0% to 52.5%, attesting to their diversity and the availability of genetic backgrounds favourable to resistance durability in the plant germplasm. The mutations in the virus genome involved in resistance breakdown also differed between plant genotypes, indicating differential selection effects exerted on the virus population by the different genetic backgrounds. The breakdown frequency was positively correlated with the level of virus accumulation, confirming the impact of quantitative resistance loci on resistance durability. Among these loci, pvr6, encoding an isoform of eIF4E, was associated with a major effect on virus accumulation and on the breakdown frequency of the pvr2 ‐mediated resistance. This exploration of plant genetic diversity delivered new resources for the control of pathogen evolution and the increase in resistance durability.